Cryptosporiopsis lomati sp. nov. on Lomatia hirsuta in Southern Argentina - Bianchinotti, Maria Virginia (2002)
Cryptosporiopsis lomati sp. nov. (Coelomycetes) is described on Lomatia hirsuta from southern Argentina. It is characterized by large, ellipsoid, fusiform to irregular conidia, pulvinate, acervular conidiomata, with branched, dense conidiophores that give rise to apical or lateral conidiogenous cells with periclinal thickenings. It is associated with spots and blackened areas on attached and/or fallen leaves.